Teachers’ and Students’ Attitudes Toward the Implementation of the Politeness Principle in Classroom Interaction (UKH Journal of Social Sciences, 2020)
Politeness is considered to promote effective interaction between people. In the process of language teaching and learning, it is believed to enhance learning by providing a lively and friendly atmosphere in the classroom (Jiang, 2010). During classroom periods, including class policy, activities, and techniques, a teacher’s language plays a critical role; it also plays an important role while giving academic instructions, motivating the class, and during the evaluation of a student’s performance and participation. This paper approaches classroom interaction from a pragmatic perspective by adopting Leech’s politeness principle and maxims. It aims to answer the following 2 questions: first, “what are the teachers’ attitudes toward the implementation of the politeness principle during classroom interactions?” and second, “what are the students’ attitudes toward the implementation of the politeness principle during classroom interactions?” To achieve the aims of this study by finding answers to the questions, the researcher prepared 2 sets of questionnaires: 1 for the teachers in the English Department and 1 for the fourth year students in the same department at the College of Basic Education, Salahaddin University-Erbil, Erbil, Iraq, for the academic year of 2018 to 2019. By analyzing the data collected, it was found that both the teachers and students have positive attitudes toward the politeness maxims and the implementation thereof during classroom interactions; furthermore, there was agreement between the teachers’ and students’ responses to the questionnaires for most of the politeness maxims except in 3 cases, which were for the maxims of sympathy, obligation (S to O), and feeling reticence.